The Effect of Audit Rotation and Audit Quality on the Concentration of the Audit Market on the Indonesia Stock Exchange - Efraim William Putra Buulolo; Oky Syahputra; Selvi Aristantya (LPPM Universitas Buddhi Dharma, 2025)
The main objective of this study is to find out and analyze the influence of audit rotation and audit quality on the concentration of the audit market on the Indonesia Stock Exchange. This study focuses on the role of audit rotation which describes the turnover of auditors that can affect the independence and objectivity of auditors, as well as the quality of audits that reflect the level of The method used in this study is multiple regression analysis, which allows researchers to test the influence of more than one independent variable on dependent variables simultaneously. The independent variables studied are audit rotation and audit quality, while the dependent variable that is the main focus of this study is the concentration of the audit market, which describes the extent to which the audit market is dominated by several large audit firms or spread across many companies. The population used in this study consisted of 84 issuers listed on the Indonesia Stock Exchange, with samples obtained through purposive sampling techniques, which resulted in 18 issuers that were studied for five years, so that the total data used reached 90 research data. The type of data used in this study is secondary data, obtained from the annual reports of issuers listed on the Indonesia Stock Exchange, as well as other relevant sources. Through data processing and multiple regression analysis, the results of this study show that audit rotation has a significant influence on the concentration of the audit market on the Indonesia Stock Exchange, which shows that changes in auditors can affect the level of market concentration. In addition, audit quality was also found to have a significant influence on the concentration of the audit market, indicating that higher audit quality can have an impact on a more equitable market distribution. Overall, this study proves that both audit rotation and audit quality have a significant influence on the concentration of the audit market on the Indonesia Stock Exchange, which provides important insights for regulators and companies in understanding the dynamics of the audit market in Indonesia.